Residual stress analysis of multi-layered buffer layers on Ni substrate for YBCO coated conductor - Arda, L.; Ataoglu, S.; Sezer, S.; Abdulaliyev, Z. (ELSEVIER SCIENCE SA, 2007)
CeO2/YSZ/CeO2 buffer layer structure is one of the preferred buffer layers for fabrication of coated conductors. Textured CeO2/YSZ/CeO2 buffer layers are grown on biaxially textured Ni (100) substrate from the solution of Zr, Y, and Ce based organometalic compounds, solvent and chelating agent using reel-to-reel sol-gel technique. The film thickness is controlled by number of coating withdrawal speed and solution chemistry. Residual stresses arise during the manufacturing process of buffer layers depending on some factors. One of the most important is due to temperature variation. Effects of the temperature variation and coating thickness on residual stress in CeO2/YSZ/CeO2 buffer layers structure annealed at high temperature are analyzed theoretically. It is observed that the stress magnitudes reach high levels in the region of interlayer of different materials. The surface morphologies and microstructure of sample are characterized by ESEM and AFM. ESEM and ATM micrographs of the films revealed pinhole-free, crack-free, smooth and dense microstructures in the used manufacturing process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: buffer layer; residual stress; sol-gel; YBCO; ZRO2 INSULATION COATINGS; CEO2 THIN-FILMS; SUPERCONDUCTING MATERIALS; TAPES; FABRICATION; DEPOSITION; GROWTH; METAL; Materials Science; Physics